The Words of Colours - Jelaska, Zrinka (Array, 2004)
The popularity of studies of colour terms following the investigation of Berlin and Kay (1969) made colour terminology one of the most famous topics in semantics. People often concentrate on the phenomenon of colour rather than of language while discussing colour and language, e.g. the dependence of the colour of the object and its texture, the colour symbolism, but the attraction of the topic may be attributed to various other reasons. This paper is another contribution to the world of colour names. It deals with colour modifying structures which enlarge the number of different words denoting colours in Croatian. They include - derivations, e.g. bjeličast, bjelkast, bjelucav, bjelušan, bjelušast, bjeluškast, which all express lesser degrees of white, prozelena "through green" - compounds, e.g. tamnocrvena, tamnocrljena, tamnorumena, which are all dark shades of red - collocations with adjectives, e.g. žarka crvena "glow red", intensifying adverbs, e.g. intenzivno crvena "inensive red", nouns rumenilo grimiza "the flush of crimson" - borrowings from other languages, including languages for special purposes, e.g. cinober "cinnabar" from German Zinober, - extensions, e.g. krvava "bloody", čađava "sooty", bakrena "cooper". As found in the literature, it is obvious that in some cases colour names lose at least some of their content and become the bearers of the meaning which is expressed by the modifiers, often based on emotional and other psycho-physical reactions of the observer. While the cross-language comparison of basic colour terms with a limited universal set of eleven (or twelve) focal colours shows that the arbitrariness of lexicalization can be constrained, next to the fact that languages differ largely in their colour terminology, these characteristics of colour words show that languages (and people) lexicalize colours arbitrarily.